Genetic and phylogenetic variations of yellowfin tuna (thunnus albacares) as a basis for sustainable fishery resources management in north moluccas - MUHAMMAD ARIS,; NEBUCHADNEZZAR AKBAR,; RUSMAWATI LABENUA, (International Journal of Pharma and Bio Sciences, 2017)
Yellowfin tuna, a big pelagic fish, is highly abundant in the waters of North Molucca. Increases fishing activities result in a decrease in population stock. The sustainability and resources status can be understood through genetically approaches. The objective of this research is to understand phylogenetic and genetic variations of yellowfin tuna in the North Molucca waters. Sample collection was done in Mei-July 2016 in the islands of Morotai, Obi, and Sanana, while the secondary data were from the islands of Ternate, Bacan, and Ambon. In total, there were 72 samples collected and analyzed. The results showed that the genetic variations of yellowfin tuna were 0.97 in Morotai, 1.00 in Sanana, 0.97 in Obi, 0.98 in Bacan, and 1.00 in Ternate and Ambon. Nucleotide variations analysis resulted 0.022 in Morotai, 0.026 in Sanana, 0.018 in Obi, 0.029 in Bacan, 0.027 in Ternate, and 0.025 in Ambon. The genetic variations value found suggests that yellowfin tuna is still in good condition based on criteria. The high variety of genetic diversity and specific haplotypes provides an illustration that there has been no genetic change in yellowfin tuna populations. Haplotype distribution analysis found 44 haplotype-specific, 11 haplotype mixed among locations, and 4 similar haplotype. Phylogenetic reconstruction showed that yellow fin tuna is panmixia population indicating all samples do not have significant genetic differences. The strategy for sustainable fishery management has to be done based on several proposed recommendations; first knowledge of genetic information on an ongoing basis covering the deployment area. Second is a population measurement based on morphological size information temporally. Third is the increase of tuna fish stock through restoking activities. The recommendations are important to be implemented in order to keep the stability and sustainability of yellow fin tuna population in the area.